Sources of Financial Assistance for Households Suffering an Adult Death in Kagera, Tanzania - Lundberg, Mattias; Over, Mead; Mujinja, Phare (World Bank, Washington, DC, 2014)
The AIDS crisis in Africa and elsewhere compels us to design appropriate assistance policies for households experience a death. Policies should take into account and strengthen existing household coping strategies, rather than duplicate or undermine them. The authors investigate the nature of coping mechanisms among a sample of households in Kagera, Tanzania in 1991-1994. They estimate the magnitude and timing of receipts of private transfers, credits, and public assistance by households with different characteristics. Their empirical strategy addresses three common methodological difficulties in estimating the impact of adult death: selection bias, endogeneity, and unobserved heterogeneity. The authors find that less-poor households (those with more physical and human capital) benefit from larger receipts of private assistance than poor households. Resource-abundant households are wealthy in social assets as well as physical assets. Poor households, on the other hand, rely relatively more on loans than private transfers, for up to a year after a death. This suggests that credit acts as insurance for households where informal interhousehold assistance contracts are not enforceable. A donor in Kagera can be sure that assistance to a wealthy household may not be able to return the favor. Assistance to the poor is more likely to come with more formal arrangements for repayment. Formal-sector assistance is targeted toward the poor immediately following the death. The impact of adult deaths on households may be mitigated either ex ante, through programs that minimize poverty and vulnerability, or ex post, by assistance targeted to the poorest and most vulnerable households. In addition, to the extent to which micro-credit programs improve access and lower the total costs of borrowing, they may not only stimulate growth and investment but also help resource-poor households overcome the impact of an adult death in the areas hard-hit by the AIDS epidemic.